2013
DOI: 10.1371/journal.pone.0064953
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activation of Sirt1 Ameliorates Polyglutamine-Induced Toxicity through the Regulation of Autophagy

Abstract: Intracellular accumulation of polyglutamine (polyQ)-expanded Huntingtin (Htt) protein is a hallmark of Huntington’s disease (HD). This study evaluated whether activation of Sirt1 by the anti-cancer agent, β-lapachone (β-lap), induces autophagy in human neuroblastoma SH-SY5Y cells, thereby reducing intracellular levels of polyQ aggregates and their concomitant cytotoxicity. Treatment of cells with β-lap markedly diminished the cytotoxicity induced by forced expression of Htt exon 1 containing a pathogenic polyQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Recently, Ramalinga et al (2015) [35] demonstrated that miR-212 inhibits autophagy by inhibiting SIRT1 expression in prostate cancer cells, while transfection of cells with SIRT1 induced autophagy. In addition, SIRT1 could reduce polyglutamine cellular toxicity by inducing autophagy in SH-SY5Y cells [36]. So far, there have been no studies examining the relationship between the SIRT1 and autophagy in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ramalinga et al (2015) [35] demonstrated that miR-212 inhibits autophagy by inhibiting SIRT1 expression in prostate cancer cells, while transfection of cells with SIRT1 induced autophagy. In addition, SIRT1 could reduce polyglutamine cellular toxicity by inducing autophagy in SH-SY5Y cells [36]. So far, there have been no studies examining the relationship between the SIRT1 and autophagy in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, overexpression of BNIP3 promoted apoptotic cell death (47,48). SIRT1, a nicotinamide adenine dinucleotide-dependent deacetylase, regulates critical metabolic and physiological processes, including autophagy (37). SIRT1 induces autophagy by forming a molecular complex with several autophagy-associated genes and directly deacetylating these components (49).…”
Section: A B C Dmentioning
confidence: 99%
“…These results indicated that curcumin promoted cell survival through inhibiting the excessive activation of autophagy by H/R. Several molecular mechanisms, including beclin-1, BN IP3 and SI RT1, respond to the regulation of autophagy (35)(36)(37). Therefore, the present study examined the changes in the levels of these autophagy-associated proteins in myocytes during H/R.…”
mentioning
confidence: 94%
“…Sirt1 knockdown suppresses autophagy; conversely, agents which activate Sirt1 tend to activate autophagy [35,83,84]. Sirt1 interacts with and directly deacetylates a number of the ATG proteins required for autophagy, including ATG5, ATG7, and ATG8 [35].…”
Section: Autophagy May Mediate Some Neuroprotective Benefits Of Ketogmentioning
confidence: 99%